2009
DOI: 10.2478/v10046-009-0010-0
|View full text |Cite
|
Sign up to set email alerts
|

Response of Lithuanian Winter Wheat Advanced Lines to Common Bunt (Tilletia tritici (BJERK.) WINT)

Abstract: Response of Lithuanian Winter Wheat Advanced Lines to Common Bunt (Tilletia tritici (BJERK.) WINT) The study was carried out at the Lithuanian Institute of Agriculture in an artificially inoculated nursery during 2006-2007. Resistance to common bunt in 2006 was tested for 71, in 2007 for 118 breeding lines of Lithuanian winter wheat from the competitive trial nursery. Additionally, 148 promising lines were selected and tested from the check nursery, which possessed some resistance in their pedigree anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Thus, they are not suitable for direct use in wheat production but can serve as donors of resistance genes in breeding programs (Ruzgas and Liatukas 2009;Matanguihan et al 2011). In compliance with this observation, the present study showed that bunt incidence was positively correlated with yield components (spike length, spikelet number and grain number in the main spike) in the progeny of 'Svilena' × A-38b cross.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, they are not suitable for direct use in wheat production but can serve as donors of resistance genes in breeding programs (Ruzgas and Liatukas 2009;Matanguihan et al 2011). In compliance with this observation, the present study showed that bunt incidence was positively correlated with yield components (spike length, spikelet number and grain number in the main spike) in the progeny of 'Svilena' × A-38b cross.…”
Section: Discussionsupporting
confidence: 75%
“…The extent of yield loss due to common and dwarf bunt in West and Northwest of Iran is estimated about %30 and %8.5 respectively, especially when seeds untreated with appropriate fungicide (Asadi & Behrozin, 1985;Mardoukhi, 1995;Sharifnabi & Hejadroud, 1992). Common bunt is the most main limitation in successful development of organic winter wheat due to a very limited number of resistant cultivars (Ruzgas & Liatukas, 2009) .The best method to control of bunts especially seed born bunts such as T. laevis and T. controversa, are using resistant cultivars and fungicides (Dumalasova & Bartos, 2010). But due to the destructive effects of chemical fungicides on the environment and natural resources, high costs and risk of pathogen resistance to fungicides, its seems that the most optimal way compatible with sustainable agriculture is using of high yielding resistant genotypes, because in addition to being effective in stability of organic agriculture, resistant cultivars are also reduce bunt incidence in the field.…”
Section: Introductionmentioning
confidence: 99%